Physical properties and stability of grapeseed oil (Vitis vinifera L.) skincare formula with gelling agent combination of Na-CMC-carbopol and HPMC-carbopol - Abdul Karim Zulkarnain; Chairunnisa Nurul Ichsani; Candriya Lael Judiantoro (Faculty of Medicine, Public Health, and Nursing Universitas Gadjah Mada and Indonesian Pharmacologist Association or Ikatan Farmakologi Indonesia (IKAFARI), 2023)
Skincare products made from natural ingredients have become the choice of many people. Grapeseed oil contains ingredients that act as a moisturizer. Na-CMC-carbopol and HPMC-carbopol are gelling agents that are widely used in preparations due to their compatibility with various materials. All three are combined to cover their respective deficiencies. This study aimed to evaluate the effect of the combination of Na-CMC-carbopol and HPMC-carbopol on the physical properties and stability of grapeseed oil gel and to determine the optimum formula. The research method was carried out by optimizing the levels of Na-CMC (2-2.5%), HPMC (2-20%), and carbopol (0.5-1%) with the Simplex Lattice Design method. Eight runs of the resulting formula were gelled and tested for their physical properties to determine the optimum formula. The optimum formula obtained was verified with statistical analysis and tested for physical stability. The stability data were analyzed statistically, 95% confidence level. The optimum formula for NaCMC-carbopol was at a concentration of 2.220% Na-CMC and 0.780% carbopol, pH 6.246 ± 0.057, spreadability 12.96 ± 0.48 cm2, adhesion 6.33 ± 0.48 sec, viscosity 166.00 ± 4.88 dPas. HPMC-carbopol at both concentrations of 1% had a pH of 4.973 ± 0.172, a viscosity of 175.20 ± 5.44 dPas, a spreadability of 18.12 ± 1.61 cm2, and an adhesion of 6.94 ± 1.68 sec. All preparations were not significantly different between predictions and experiments. The optimum gel formula had good physical properties and was stable during 3 cycles of cycling stability test.